Descriptions of the adult male and female genitalia of the genus Osobenus Ricker (Plecoptera: Perlodidae) - Sandberg, John B. (Illiesia, 2015)
The male and female terminalia of the perlodine Osobenus yakimae (Hoppe 1938) are described, supported by scanning electron micrographs and color images. The distinctive epiproct of the male is described in detail for the first time. The paired dorsal membranous processes of the epiproct terminating in 6-7 large external spinulae processes appear unique within the Diploperlini of the Perlodinae.
Keywords: entomology; stoneflies; Perlodidae; Plecoptera; Osobenus; genitalia descriptions